Paving the way to net-zero: identifying environmental sustainability factors for business model innovation through carbon disclosure project data - Asif, Muhammad Salman; Lau, Henry; Nakandala, Dilupa; Hurriyet, Hilal (Frontiers in Sustainable Food Systems, 2023)
Net-zero emission targets are crucial, given the environmental impact of the food and beverage industries. Our study proposes an environmentally focused Sustainable Business Model (SBM) using data from 252 food, beverage, and tobacco companies that reported to the Carbon Disclosure Project (CDP). We investigated the risks, opportunities, business strategies, emission reduction initiatives, and supply chain interactions associated with climate change by analyzing their qualitative answers using the NVivo software. Following the grounded theory approach, we identified the Environmental Sustainability Factors (ESFs) that support businesses in meeting pollution reduction targets. The ESFs were integrated with Osterwalder's business model canvas to create an archetype focused on delivering “net-zero” or “carbon neutral” value to customers. The model's efficacy is enhanced by the advantages and motivations of environmental collaborations. The paper provides critical support for sustainability theories and assists Small and Medium Enterprises (SMEs) to develop strategic business models for net-zero emission targets.